Job Safety Analysis (JSA) Implementation In Effort To Reduce Work Accidents At PT Geoservices In Sangatta - Selvi Sampe (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
Occupational Safety and Health (K3) is the main means for the prevention of workplace accidents, disabilities, and deaths for employees. One way to identify hazards is to use a work safety analysis or better known as the Job Safety Analysis (JSA), which can examine work methods and find hazards from the design of machines, tools, materials, environment, and work processes needed for workers to prevent interference with work safety. This study aims to analyze and determine the implementation of Job Safety Analysis (JSA) to reduce the number of work accidents at PT. Geoservices Sangatta. Job Safety Analysis (JSA) (X) is used as an independent variable while Work Accident (Y) is the dependent variable. Primary data obtained through interviews directly with 5 employees of PT. Geoservices Sangatta. Secondary data obtained through data that is already available at PT. Geoservices Sangatta. The results showed that in the process of carrying out the work of PT. Geoservices Sangatta had made a policy that was committed to implementing occupational safety and health, as well as identifying hazards and prevention at each stage of the job namely by Job Safety Analysis (JSA). The implementation of Job Safety Analysis (JSA) at PT. Geoservices Sangatta can reduce the number of work accidents as seen from the decreasing number of work accidents that occurred at PT. Geoservices Sangatta in early 2020, although in the implementation there are still some lacking especially in the implementation of safety talk which only runs documents or administration, in practice, they are not routinely carried out. PT. Geoservices Sangatta should follow up with the socialization of Job Safety Analysis (JSA) procedures to all employees, one of which is by conducting training on occupational safety and health so that all employees truly understand and realize how important K3 is to employee safety and health.